Philosophical elements of human rights in the identity worldview of the Wiwa indigenous people of the Sierra Nevada of Santa Marta, Colombia - Fonseca Lidueña, Carlos Milton (EUNOMÍA. Revista en Cultura de la Legalidad, 2025)
The philosophical foundation of human rights has generally been studied from the considerations of rationalist and normativist natural law and positivism without taking into account cultural diversity and the different conceptions of human rights that ethnic community have within a society. Therefore, in this article, legal-philosophical elements of human rights will be analyzed from the perspective of the cultural identity of the Wiwa indigenous people of the Sierra Nevada de Santa Marta, through the study of their social practices as necessary tools for them to be respected. guarantee and adapt their fundamental rights, through intercultural translations carried out with dialogical and diatopic reasoning in order to practically resolve complex problems derived from multiculturalism related to discordant values and conflicting perspectives of cultures concerned.
Keywords: Foundation; human rights; cultural identity; interculturality